The Effect of Nutrition Education Using E-Module Media Toward Fiber Intake in Overweight Female Adolescent - Hidayatusy Syukrina Puteri; Yulia Lanti Retno Dewi; Sri Mulyani (Global Health Science Group, 2023)
One of the factors causing excess nutritional status in female adolescent (FA) is due to the lack of fiber consumption. The West Sumatra Riskesdas 2019: 82.53% of adolescents in Padang consume less fiber and the prevalence of overweight among FA is higher than male adolescents of 16.45%. Some literature states that one of the interventions to increase the awareness and motivate the FA to consume fiber is nutrition education (NE) by using attractive media. E-module is one of the attractive media and frequently used in the learning process. The material presentation is not merely focus on the text, picture, and graphic, however it is also presenting audio, animation, and video. The purpose of this research is to analyze the effect of NE using e-module media toward the fiber intake in overweight FA. This is a mix (R&D and quasi-experiment) research methods of one group pretest and posttest with control designs. The research subjects were all female students at research target schools who met the inclusion and exclusion criteria. The data instrument used the SQ-FFQ form. The data analysis is using a Mann Whitney test. The results of the study explained that the designed nutritional e-module obtained an average validation value namely 90.5% and the practical value of the overall was 92.83%. The results of the Man Whitney test showed that there was an effect of NE with the e-module and it was very effective toward the change of fiber intake for overweight FA in Padang p-value 0.017 (p<0.05).